75. Less is More: A Physician-Driven Quality Improvement Stewardship Initiative to Reduce Excessive Duration of Antibiotic Therapy in Veterans Hospitalized with Community-Acquired Pneumonia. (31st December 2020) - Monday, Lea M; Yazdanpanah, Omid; Sokolowski, Caleb; Sebastian, Joseph; Kuhn, Ryan; Kareem, Bazzy; Dhar, Sorabh
Abstract: Background: The IDSA and American Thoracic Society (IDSA/ATS) Community Acquired Pneumonia (CAP) guidelines recommend 5 days of therapy for clinically stable patients that defervesce, however, duration of therapy (DOT) is often longer. Pharmacists curb this via antimicrobial stewardship (AMS), but budgetary constraints are barriers to robust AMS programs in some hospitals. Physicians are increasingly encouraged to participate in quality improvement (QI) and are a potential resource to improve AMS. We sought to determine the impact of a prospective, physician-driven stewardship intervention on DOT and clinical outcomes in hospitalized veterans with CAP, with the goal to reduce the median DOT by at least 1 day within 5 months. Methods: This single center, quasi-experimental QI study evaluated two concurrent physician-driven interventions over a 5-month period in an inner-city Veterans Affairs Hospital. Using DMAIC (Define, measure, analyze, improve, and control) methodology, the Chief Resident in Quality and Safety (CRQS) provided monthly education and daily audit and feedback with patient-specific DOT recommendations. Clinical outcomes were followed until 30 days post discharge. Results: A total of 123 patients with CAP were included (57 in the historic control group and 66 in the AMS intervention group). The AMS intervention significantly increased the proportion of CAP patients treated with a 5-day treatment course (56% versus 5.3%, p< 0.0001), and reduced the proportion of patients treated beyond 7 days (12.1% versus 70.2%, p< 0.0001). Median DOT per patient was reduced significantly (5 versus 8 days, p< 0.0001). Median excess antibiotic days were significantly reduced (0 versus 3, p< 0.0001) and 118 days of unnecessary antibiotics were avoided (62 versus 180). 30-day all-cause mortality, all-cause readmission, and Clostridium difficile infection were similar between groups. Median LOS was similar between groups (p=0.246). DOT in the Historic Control Group Versus Stewardship Intervention Group Conclusion: A physician driven QI stewardship intervention in hospitalized CAP patients significantly reduced the total antibiotic DOT and excess antibiotic days without adversely affecting patient outcomes. Providers can be educated through physician driven interventions resulting in substantial improvements in appropriate antibiotic use. Disclosures: All Authors : No reported disclosures